Manusia Pontifical dalam Diskursus Modernitas: Studi Komparasi Pemikiran S.H. Nasr dan Carl G. Jung - Mahmudi Mahmudi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
Abstract: This article analyzes Nasr’s thoughts concerning human spirituality and compares Jung’s perspective on the Human soul in the modern era. This article uses a comparative study with a hermeneutical approach to the understanding meaning of spirituality in the contemporary era. The method of this study is library research focusing on Man and Nature and Modern Man in Search of the Soul written by Nasr and Jung. The author uses content analysis to understand the book written by Nasr and Jung. This article concludes that spirituality is critical in modern era as a discourse on religion and humanity.